2021
DOI: 10.1182/blood.2020006252
|View full text |Cite|
|
Sign up to set email alerts
|

Neighborhood poverty and pediatric allogeneic hematopoietic cell transplantation outcomes: a CIBMTR analysis

Abstract: Social determinants of health, including poverty, contribute significantly to health outcomes in the United States, yet their impact on pediatric hematopoietic cell transplantation (HCT) outcomes is poorly understood. We aimed to identify the association between neighborhood-poverty and HCT outcomes for pediatric allogeneic HCT recipients in the Center for International Blood and Marrow Transplant Research (CIBMTR) database. We assembled two pediatric cohorts who received a first, allogeneic HCT from 2006-2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 43 publications
1
34
3
Order By: Relevance
“…The parental LEP group was more likely to self‐identify as having financial strain at the time of pretransplant evaluation and these children were more likely to have government‐sponsored Medicaid, both of which suggest likely differences in socioeconomic status. A large pediatric transplant database analysis recently demonstrated inferior overall survival in children with Medicaid as compared to children with private insurance among pediatric patients receiving allogeneic transplant for malignant diseases 49 …”
Section: Discussionmentioning
confidence: 99%
“…The parental LEP group was more likely to self‐identify as having financial strain at the time of pretransplant evaluation and these children were more likely to have government‐sponsored Medicaid, both of which suggest likely differences in socioeconomic status. A large pediatric transplant database analysis recently demonstrated inferior overall survival in children with Medicaid as compared to children with private insurance among pediatric patients receiving allogeneic transplant for malignant diseases 49 …”
Section: Discussionmentioning
confidence: 99%
“…For patients with unspecified malignant disease who received hematopoietic cell transplant treatment, those on public insurance (Medicaid) had higher probability of all-cause mortality. 36 Some studies found no association between insurance and survival.…”
Section: Sdoh Domain 3: Health and Healthcarementioning
confidence: 99%
“…The disparity between malignant and nonmalignant conditions is intriguing, and possibly a result of a selection bias in the nonmalignant cohort, in which often HSCT is not the first-line treatment option. 111 In the posttransplant period, 34% of patients with long-term graft-vs-host disease had experienced delayed/denied treatments for their condition contributing to their financial hardship. 112 A multidisciplinary approach including psychosocial and sociodemographic assessments can help mitigate these challenges.…”
Section: Social Determinants Of Prevention and Diagnosis Of Primary I...mentioning
confidence: 99%